2024
DOI: 10.1039/d3sm01444d
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions of fluorotelomer alcohols at the water|alkane interface studied via molecular dynamics simulation

Stephen A. Burrows,
Jang Won Shon,
Boyan Peychev
et al.

Abstract: Fluorosurfactants are long-lasting environmental pollutants that accumulate at interfaces ranging from aerosol droplet surfaces to cell membranes. Modeling of adsorption-based removal technologies for fluorosurfactants requires accurate simulation methods which can...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…To achieve the set goal, we collected tensiometric data for the three shortest watersoluble fluorotelomer alcohols of the type F(CF 2 ) n CH 2 OH, with n = 1, 2, 3, adsorbing on the water|hexane interface (see Table 1). The particular choice of alcohols as surfactants and hexane as the oil phase was based on the large amount of previous work done for similar systems, usually with longer oil-soluble homologues; this includes experimental [32][33][34][35][36][37][38], theoretical [25], and simulation studies [39]. Furthermore, we also investigated the temperature dependence of ∆µ CF 2 in the range 288.15-303.15 K. For the analysis of the tensiometric data, we used the sticky disk adsorption model [40,41] and the molecular thermodynamic model for K a of Ivanov et al [21,22,41], both of which were shown previously to work well for longer oil-soluble fluorotelomer alcohols [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve the set goal, we collected tensiometric data for the three shortest watersoluble fluorotelomer alcohols of the type F(CF 2 ) n CH 2 OH, with n = 1, 2, 3, adsorbing on the water|hexane interface (see Table 1). The particular choice of alcohols as surfactants and hexane as the oil phase was based on the large amount of previous work done for similar systems, usually with longer oil-soluble homologues; this includes experimental [32][33][34][35][36][37][38], theoretical [25], and simulation studies [39]. Furthermore, we also investigated the temperature dependence of ∆µ CF 2 in the range 288.15-303.15 K. For the analysis of the tensiometric data, we used the sticky disk adsorption model [40,41] and the molecular thermodynamic model for K a of Ivanov et al [21,22,41], both of which were shown previously to work well for longer oil-soluble fluorotelomer alcohols [25].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve the set goal, we collected tensiometric data for the three shortest water-soluble fluorotelomer alcohols of the type , with , adsorbing on the water|hexane interface (see Table 1 ). The particular choice of alcohols as surfactants and hexane as the oil phase was based on the large amount of previous work done for similar systems, usually with longer oil-soluble homologues; this includes experimental [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ], theoretical [ 25 ], and simulation studies [ 39 ]. Furthermore, we also investigated the temperature dependence of in the range 288.15–303.15 K.…”
Section: Introductionmentioning
confidence: 99%